Prenatal, perinatal, and neonatal factors associated with self-injurious behaviors in children with autism spectrum disorder. (May 2019) - Soke, Gnakub Norbert; Rosenberg, Steve A.; Hamman, Richard F.; Fingerlin, Tasha E.; Rosenberg, C. Robinson; Carpenter, Laura; Lee, Li-Ching; Giarelli, Ellen; Wiggins, Lisa D.; Durkin, Maureen S.; DiGuiseppi, Carolyn
Abstract: Background: Studies that examine the role of factors documented before self-injurious behaviors (SIB) occur are important in establishing a temporal relationship between these factors and SIB. Using data from a population-based surveillance system of 8-year-olds with autism spectrum disorder (ASD), we: (1) explored potential associations between SIB and prenatal, perinatal, and neonatal factors identified from birth certificates, and 2) validated associations between SIB and developmental, behavioral, medical factors accounting for the above prenatal, perinatal, and neonatal factors. Methods: We included 4343 children from the Autism and Developmental Disabilities Monitoring Network from the 2000, 2006, and 2008 surveillance years. Prenatal, perinatal and neonatal characteristics were obtained from birth certificates. SIB and other potential risk factors were abstracted from children's health or education records. The associations between SIB and various potential risk factors were tested using non-linear mixed models. Results: Lower maternal educational attainment (adjusted odds-ratio [aOR]: 1.35 [95% confidence interval 1.10–1.67]), prenatal maternal cigarette smoking (1.47 [1.09–1.98]), and electronic fetal monitoring during labor (1.70 [1.02–2.84]) were associated with SIB. In addition, we validated previous associations between SIB and developmental regression, lower IQ, behavioral, sensory and sleep problems, co-occurring developmental and psychiatric diagnoses. Conclusions: The associations between SIB and maternal smoking, low maternal education attainment may be due to various factors, including low SES and limited access to specialized ASD services. Electronic fetal monitoring may be a marker for unmeasured perinatal complications. Findings reported in this study have implications for better understanding of factors associated with SIB to guide prevention and interventions.